2014
DOI: 10.1037/a0036748
|View full text |Cite
|
Sign up to set email alerts
|

Positive messaging promotes walking in older adults.

Abstract: Walking is among the most cost-effective and accessible means of exercise. Mounting evidence suggests that walking may help to maintain physical and cognitive independence in old age by preventing a variety of health problems. However, older Americans fall far short of meeting the daily recommendations for walking. In two studies, we examined whether considering older adults’ preferential attention to positive information may effectively enhance interventions aimed at promoting walking. In Study 1, we compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
108
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 78 publications
10
108
2
Order By: Relevance
“…Consistent with other research 1,17,18 , consultations with consumers and carers highlighted key elements that might resonate with people in this age group. Rather than overly prescriptive, ageist or paternalistic messaging that simply focuses on the harms of alcohol use, more creative, humorous and playful content might be better received.…”
Section: Conclusion and Implications For Health Promotion Practicesupporting
confidence: 56%
See 1 more Smart Citation
“…Consistent with other research 1,17,18 , consultations with consumers and carers highlighted key elements that might resonate with people in this age group. Rather than overly prescriptive, ageist or paternalistic messaging that simply focuses on the harms of alcohol use, more creative, humorous and playful content might be better received.…”
Section: Conclusion and Implications For Health Promotion Practicesupporting
confidence: 56%
“…We drew on positive messaging and incorporated humour -both of which have been shown to be useful in engaging people aged 55 and older in behaviour change 17,18 -to motivate individuals to find their own strategies to manage stress without relying on alcohol. The animation was developed in PowToon, an easy-to-use and low-cost animation development program that uses precreated images.…”
Section: Research Into Action: Developing the Animationmentioning
confidence: 99%
“…Recently, Notthoff and Carstensen (2014) showed that-in line with the positivity effect-positively framed messages promoted walking in older adults better than negatively framed messages. In this study, we examined the role of memory and motivation as mechanisms that presumably underlie the greater effectiveness of positively framed compared to negatively framed messages about physical activities.…”
Section: Discussionmentioning
confidence: 95%
“…Recent research shows that message framing which takes into account age differences in motivation effectively promotes walking in older adults (Notthoff and Carstensen 2014). In two studies, older adults who received positively framed messages about the benefits of walking increased walking significantly more than their peers who received negatively framed messages about the risks of failing to walk more.…”
mentioning
confidence: 99%
See 1 more Smart Citation